Organisational mental health. - Chua, Pin Sin. (2008)
As organisational mental health (OMH) in Singapore is not well developed compared to the Western countries, this study was done in an attempt to examine the OMH scene in Singapore. It consists of two sections: a literature survey of a number of existing journal articles, and an empirical study on a sample of 180 nurses in a general hospital in Singapore.